Cardiac magnetic resonance patterns of left ventricular remodeling in patients with severe aortic stenosis referred to surgical aortic valve replacement - Rita Reis Santos; João Abecasis; Sérgio Maltês; Pedro Lopes; Luís Oliveira; Pedro Freitas; António Ferreira; Regina Ribeiras; Maria João Andrade; Miguel Sousa Uva; José Pedro Neves; Victor Gil; et al. (Scientific Reports, 2024)
Abstract Left ventricular (LV) hypertrophy is a common finding in patients with severe aortic stenosis (AS). Cardiac magnetic resonance (CMR) is the gold-standard technique to evaluate LV remodeling. Our aim was to assess the prevalence and describe the patterns of LV adaptation in AS patients before and after surgical aortic valve replacement (AVR). Prospective study of 130 consecutive patients (71y [IQR 68–77y], 48% men) with severe AS, referred for surgical AVR. Patterns of LV remodeling were assessed by CMR. Besides normal LV ventricular structure, four other patterns were considered: concentric remodeling, concentric hypertrophy, eccentric hypertrophy, and adverse remodeling. At baseline CMR study: mean LV indexed mass: 81.8 ± 26.7 g/m2; mean end-diastolic LV indexed volume: 85.7 ± 23.1 mL/m2 and median geometric remodeling ratio: 0.96 g/mL [IQR 0.82–1.08 g/mL]. LV hypertrophy occurred in 49% of subjects (concentric 44%; eccentric 5%). Both normal LV structure and concentric remodeling had a prevalence of 25% among the cohort; one patient had an adverse remodeling pattern. Asymmetric LV wall thickening was present in 55% of the patients, with predominant septal involvement. AVR was performed in 119 patients. At 3–6 months after AVR, LV remodeling changed to: normal ventricular geometry in 60%, concentric remodeling in 27%, concentric hypertrophy in 10%, eccentric hypertrophy in 3% and adverse remodeling (one patient). Indexes of AS severity, LV systolic and diastolic function and NT-proBNP were significantly different among the distinct patterns of remodeling. Several distinct patterns of LV remodelling beyond concentric hypertrophy occur in patients with classical severe AS. Asymmetric hypertrophy is a common finding and LV response after AVR is diverse.